2022
DOI: 10.1007/s00068-021-01835-5
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization and satisfaction with treatment before and after direct discharge from the Emergency Department of simple stable musculoskeletal injuries in the Netherlands

Abstract: Purpose To evaluate healthcare utilization and satisfaction with treatment before and after implementing direct discharge (DD) from the Emergency Department (ED) of patients with simple, stable musculoskeletal injuries. Methods Patients with simple, stable musculoskeletal injuries were included in two Dutch hospitals, both level-2 trauma centers: OLVG and Sint Antonius (SA), before (pre-DD-cohort) and after implementing DD (DD-cohort). With DD, no routine follow-up appo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Most health care professionals considered DD a safe alternative to face-to-face follow-up, leading to a perceived reduction of SHU. This finding is consistent with previous articles, which concluded that DD is safe based on low, comparable complication numbers, with significantly reduced SHU compared to traditional treatment [9,18,33]. The perceived reduction in SHU varied among stakeholders.…”
Section: Comparison With Existing Literaturesupporting
confidence: 90%
See 1 more Smart Citation
“…Most health care professionals considered DD a safe alternative to face-to-face follow-up, leading to a perceived reduction of SHU. This finding is consistent with previous articles, which concluded that DD is safe based on low, comparable complication numbers, with significantly reduced SHU compared to traditional treatment [9,18,33]. The perceived reduction in SHU varied among stakeholders.…”
Section: Comparison With Existing Literaturesupporting
confidence: 90%
“…The DD protocol involves discharging patients from the emergency department (ED) without scheduled follow-up while providing patients with information through a self-care mobile eHealth app. DD significantly reduces secondary health care use (SHU) with similar levels of patient satisfaction and primary health care use (PHU) [9][10][11]. Based on these results and catalyzed by the COVID-19 pandemic, over 25 Dutch hospitals have implemented this protocol since 2019 [12].…”
Section: Introductionmentioning
confidence: 99%
“…22 Moreover, in a previous Dutch cohort study it was shown that the direct discharge of simple, stable musculoskeletal injuries from the ED is feasible. 23 Our findings support the idea that the low-acuity nature of the Further research is needed to evaluate this alternate clinical pathway and its effect on patient care, missed injury rates and ED crowding.…”
Section: Discussionsupporting
confidence: 78%
“…This was illustrated during the COVID‐19 pandemic, in which a considerable number of Dutch EDs redirected patients with minor traumatic injuries to outpatient departments 22 . Moreover, in a previous Dutch cohort study it was shown that the direct discharge of simple, stable musculoskeletal injuries from the ED is feasible 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation